2022
DOI: 10.1016/j.bioactmat.2021.08.031
|View full text |Cite
|
Sign up to set email alerts
|

High proportion strontium-doped micro-arc oxidation coatings enhance early osseointegration of titanium in osteoporosis by anti-oxidative stress pathway

Abstract: The excessive accumulation of reactive oxygen species (ROS) under osteoporosis precipitates a microenvironment with high levels of oxidative stress (OS). This could significantly interfere with the bioactivity of conventional titanium implants, impeding their early osseointegration with bone. We have prepared a series of strontium (Sr)-doped titanium implants via micro-arc oxidation (MAO) to verify their efficacy and differences in osteoinduction capabilities under normal and osteoporotic (high OS levels) cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 63 publications
4
62
0
Order By: Relevance
“…Notably, the bio-MOFs were in a mixed valence state with an increase of the Ce 4+ /Ce 3+ ratio from AHT-CeMOF to AHT-Ce/SrMOF. Recent studies revealed that increasing the Ce 4+ /Ce 3+ ratio endowed materials with a strong enzyme mimic activity and promoted cell proliferation …”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Notably, the bio-MOFs were in a mixed valence state with an increase of the Ce 4+ /Ce 3+ ratio from AHT-CeMOF to AHT-Ce/SrMOF. Recent studies revealed that increasing the Ce 4+ /Ce 3+ ratio endowed materials with a strong enzyme mimic activity and promoted cell proliferation …”
Section: Resultssupporting
confidence: 83%
“…Hence, developing biomaterials with antioxidant properties to reprogram MSCs holds considerable promise for repairing osteoporotic bone defects. Interestingly, Ce is a rare-earth element with versatile catalytic functions, which has attracted broad interest for the intervention against osteoporosis-related indications. Specifically, Ce ion could demonstrate similar catalytic functions like endogenous antioxidant enzymes such as catalase (CAT) and superoxide dismutase (SOD) to mediate the detoxification of ROS, which could contribute to eliminate the oxidative stress in the osteoporotic microenvironment. , Additionally, some studies proved that Sr could promote the CAT/SOD activity and modulate mitochondrial dynamics for enhanced diabetic osseointegration. , Therefore, Ce and Sr ions could be exploited to coordinatively mediate the resurgence of mitochondrial dynamics in MSCs for functional restoration and enhancing osteogenicity. , Nevertheless, despite the therapeutic promise of the rare-earth metal ions, their therapeutic transition into clinics is impeded by the potential short-term and long-term cytotoxic impacts after accidental leakage, thus warranting new Ce/Sr delivery strategies with improved precision, safety, and efficacy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Through simulating a microenvironment with high levels of OS, Shen et al used samples with different levels of strontium doping (25%, 75%, 100%) to investigate how strontium affects bone regeneration by regulating ROS production and found that high Sr-doped samples (especially Sr100%) had positive effects on osteoimmunomodulation under the OS microenvironment. This may be related to the fact that a high dose of Sr2+ effectively eliminates the excessive accumulation of endogenous ROS in osteoblasts by enhancing the activity of CAT and SOD in the body; meanwhile, Sr2+ inhibits ROS production and alleviates the level of inflammation to affect the cytoarchitecture and CAT/SOD activity of macrophages, which promotes the polarization of M0 macrophages to M2 ( Shen et al, 2022 ). Therefore, further research on the anti-oxidative stress mechanism of strontium-doped biomaterials and the use of new smart strontium-doped biomaterials to regulate OS in the body may be one of the strategies to promote bone repair.…”
Section: Immunological Mechanism Of Strontium For Osteogenesismentioning
confidence: 99%
“…Shen et al successfully fabricated Sr-doped titanium surface coatings. In large-proportion strontium-doped materials (75–100%), the expression of anti-inflammatory cytokines (e.g., IL-10) and osteogenesis-related genes (e.g., TGF-β1) increases when compared to Ti (Sr content 0%), while the expression of inflammation-favoring genes (e.g., TNF-α) decreases significantly [ 115 ]. The high-Sr samples prominently encourage macrophage polarization from M0 to M2, creating a favorable milieu for regulating OIM [ 116 ].…”
Section: Biomaterial-mediated Bone Regeneration Immune Responsementioning
confidence: 99%